O valor econômico da educação formal: um estudo a nível de propriedade rural no sul do Brasil - Cusumano, V.; Kirst, P.H.; Rezende, José P. de; Giuliani, B. (Revista do Centro de Ciências Rurais, 2008)
Este trabalho foi elaborado com o propósito de estimar o efeito da educação formal sobre um grupo de agricultores. Comparando três grupos de agricultores do municipio de Santa Maria, RS, classificados segundo nível de educação atingido, verificou-se que existem diferenças significativas na renda agricola e na eficisncia obtida na utilizapho dos insumos. A renda agrícola estimada para o grupo de agricultores sem educação formal foi de Cr 6.070,00 por ano (1970) e Cr 25.461,00 para o grupo de agricultores com o primário completo ou mais. Estimou-se, além disso, um retorno adicional de Cr 0,70 para cada cruzeiro gasto em capital pelos agricultores sem escolaridade formal. Porém, este retorno foi estimado a Cr 2,23 para os agricultores com o primário completo ou mais. Conclui-se que o investimento educacional no município de Santa Maria teria um benefício positivo para os agricultores do município Abstract The principal objective of this study was to estimate the economic value of formal education for farmers in Santa Maria County, RS. A sample of 230 farmers was divided into three groups according to their educational level. Comparing the three groups, it was observed that significant differences existed in farm income, and in the manner that these farmers utilized their resources. Farm income was estimated at Cr 6.070,00 per annum for those farmers without any formal education and at Cr 25.461,00 for those farmers with at least a primary education completed. The marginal value productivities for labor, land, capital and managerial ability were also estimated using a linear production functian. Significant differences ware found in the economic efficiency of capital use. The marginal productivity of capital for those farmers with no formal education was estimated at Cr 0,70, while for those farmers with a primary education completed the marginal value productivity was estimated at Cr 2,23. It was also conclued that additional investment in education for farmers in Santa Maria county would have a positive effect on farm income and overall farm efficiency.